MoEnd3 regulates appressorium formation and virulence through mediating endocytosis in rice blast fungus Magnaporthe oryzae. - Xiao Li (PLoS Pathogens, 2017)
Eukaryotic cells respond to environmental stimuli when cell surface receptors are bound by environmental ligands. The binding initiates a signal transduction cascade that results in the appropriate intracellular responses. Studies have shown that endocytosis is critical for receptor internalization and signaling activation. In the rice blast fungus Magnaporthe oryzae, a non-canonical G-protein coupled receptor, Pth11, and membrane sensors MoMsb2 and MoSho1 are thought to function upstream of G-protein/cAMP signaling and the Pmk1 MAPK pathway to regulate appressorium formation and pathogenesis. However, little is known about how these receptors or sensors are internalized and transported into intracellular compartments. We found that the MoEnd3 protein is important for endocytic transport and that the ΔMoend3 mutant exhibited defects in efficient internalization of Pth11 and MoSho1. The ΔMoend3 mutant was also defective in Pmk1 phosphorylation, autophagy, appressorium formation and function. Intriguingly, restoring Pmk1 phosphorylation levels in ΔMoend3 suppressed most of these defects. Moreover, we demonstrated that MoEnd3 is subject to regulation by MoArk1 through protein phosphorylation. We also found that MoEnd3 has additional functions in facilitating the secretion of effectors, including Avr-Pia and AvrPiz-t that suppress rice immunity. Taken together, our findings suggest that MoEnd3 plays a critical role in mediating receptor endocytosis that is critical for the signal transduction-regulated development and virulence of M. oryzae.